FPGA Verification and ASIC Implementation of a Load Carrying Follower Cart - D. Gabi, Richmond; Grace M. Sarmiento, Angel; Joy L. Gerasta, Olga; A. Hora, Jefferson; Banuchandar, J. (International Journal of Engineering and Technology, 2018)
A Follower Cart system is designed using Verilog Hardware Description Language (HDL) and implemented in an Application Specific Integrated Circuit (ASIC). A prototype that is capable of carrying 0 kg load is developed with the use of Field Programmable Gate Array (FPGA) as its controller for debugging and verification. The study then acquired a chip level layout of the control system with an area of 498.94 µm that has a power consumption of 0.4981 mW and cell leakage power of 19.49 µW. The output of this study allows mass production of a dedicated IC for a Load Carrying Follower Cart control system which is more efficient in terms of unit cost and power consumption